Understanding the Roles of Religion in Nursing Practice as a Prescriptive Instrument for High-Quality Faith-Based Healthcare - Olaolorunpo Olorunfemi; Oluwapamilerinayo Cynthia Agbaje; Oluwaseun Oluwafunmilayo Abiodun; Bamidele Abiodun Ayeni; Rosemary Ngozi Osunde (Amrita Journal of Medicine)
Religion is the patient’s belief in a higher power. This power could have a significant impact on the care provided by nurses. Therefore, it is important to examine the role of religion in providing holistic and faith-based nursing care. The objective of this study is to assess the roles of religion in nursing practice. This study reviewed previous works of literature and screened for eligibility, with the search years of 2018–2024 to capture the identified variables in the review objectives. In our literature search, we discovered various ways in which religion intersects with nursing practice, shaping attitudes, beliefs, decision-making processes, and holistic patient care through transcultural nursing theory. In conclusion, we discovered that religion has a diverse and significant role in nursing practice, influencing both professional aspects of caregiving and patient well-being; it brings strength, hope, comfort, and resilience. All of these help patients cope with anxiety, stress, and depression while improving the overall health outcomes. It is therefore essential that nurses acquire at least a basic knowledge of the most common religions to provide holistic care that meets their patients’ needs. We also encourage nurses to work following their clients’ religious beliefs and not discriminate when they differ from their own.